Preserving vaginal health after treatment for gynecological malignancies - A. G. Kedrova (Опухоли женской репродуктивной системы)
The prevalence of vaginal atrophy is particularly high among women who have undergone treatment for gynecological cancers, since they have significantly lower estrogen levels and altered vaginal microbiota. These patients often experience vaginal discomfort, dryness, and pain, but rarely report this to a doctor. Such symptoms affect patients’ quality of life and might cause a family breakdown. This article proposes a safe therapeutic option for women with vulvovaginal atrophy resulted from gynecological surgeries or comprehensive treatment for gynecological cancers. It provides a rationale for the local application of Estrogial™ containing hyaluronic acid. Elimination of symptoms, such as burning, itching, swelling, and hyperemia of the vulval vestibule and perineal tissues ensured maximum compliance to treatment in cancer patients and improved their quality of life after combination therapy.